Trabalho infantil e cultura camponesa: interpelações às políticas públicas - Thais Barbosa Reis; Maria Dione Carvalho de Moraes (Ciências Sociais Unisinos)
The addressing of child labor became a part of the Brazilian state agenda in the 1990s, anchored in the discourse on the human rights of children. But the addressing of that problem through public policies to combat child labor meets resistance in peasant socie-ties, in which children are socialized through work. In this perspective, this article aims to analyze the convergence and divergence, in the arena of legitimacy, between peasant culture and the policies designed to eradicate child labor. This important analysis is part of the author’s doctoral dissertation on public policies that is in progress. Its methodol-ogy is based on the systematic analysis of bibliographical and documentary sources, aiming to point out dilemmas, tensions and paths, at the conceptual level, regarding that relationship. Child labor must be combated, especially in the peasant world, in which children and adolescents are exposed to particular risks of agriculture, although it is a subsistence agriculture. However, public policies designed to eradicate child labor need to dialogue with the socio-cultural particularities of this world, so that they can be constructed having legitimacy and effectiveness.